PENYELESAIAN SENGKETA PERJANJIAN KERJASAMA ANTARA PT. SAFARI RIAU DENGAN KOPERASI TERANTANG JAYA MANDIRI DESA TERANTANG MANUK KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Tengku Indira Larasati; Zulfikar Jaya Kusuma; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The government in the context of plantation management has directed its attention to increase the productivity of plantation management through partnership patterns. People who have low education who as a whole do not understand what and how the pattern of partnerships and lack of understanding in legal and management knowledge do not rule out the possibility of causing irregularities in a partnership agreement for the benefit of the core company, as happened at PT. Riau Safari. PT. Safari Riau as a partner of oil palm farmers should build a reciprocal relationship as a mutually beneficial partner. The partnership agreement that should have been mutually beneficial in the development cooperation and management of oil palm plantations caused polemic problems that resulted in a dispute between PT. Safari Riau and Koperasi Terantang Jaya Mandiri.This study aims to determine the rights and obligations of a cooperation agreement between PT. Safari Riau and the Koperasi Terantang Jaya Mandiri and the resolution of the dispute in the development and management of palm oil in Terantang Manuk Village, Pangkalan Kuras District. This research is an analytical descriptive empirical study. Data collection techniques carried out using primary data and secondary data. The results showed that 1) Rights and obligations of PT. Safari Riau and Koperasi Terantang Jaya Mandiri in the Palm Oil Development and Management Cooperation Agreement in the Terantang Manuk Village in Pangkalan Kuras Subdistrict, namely the company's rights as a manager and to finance the development and management of oil palm on the land of Kop-TJM members by providing experts for the development and management of plsama and providing technical guidance and job training to all workers and members. Kop-TJM is required to repay loans and will not sell or transfer ownership rights to plasma plantations without company approval. The rights of Kop-TJM members are obtained from the FFB sales revenue distributed monthly based on a percentage of FFB sales revenue. 2) Settlement of Disputes between PT. Safari Riau with the Terantang Jaya Mandiri Cooperative in the Development and Management of Palm Oil in the Terantang Manuk Village, Pangkalan Kuras District has been carried out through several stages, namely the stages of negotiation, conciliation and mediation. PT. Safari Riau with the Koperasi Terantang Jaya Mandiri in the Development and Management of Palm Oil in the Terantang Manuk Village, Pangkalan Kuras District continued until the court's verdict.Keywords: Settlement of Disputes - Cooperation Agreements – Cooperatives